Factores de riesgo ergonómicos que inciden en los trastornos musculoesqueléticos en el personal de enfermería del Hospital Universitario de Guayaquil periodo junio-octubre del 2023. - Rea Rea, Johanna Abigail (2023)
MSDs of occupational origin develop over time due to repeated or prolonged exposure to unfavorable situations in the performance of work, or due to inadequate handling of loads. Therefore, the objective is to: Establish the main ergonomic risk factors that affect musculoskeletal disorders in the nursing staff of the University Hospital of Guayaquil during the period June-October 2023. The project is developed based on basic research. . with quantitative modality using inductive methods and analysis; With a sample of 30 people, because the intentional non-probabilistic method was applied based on this, the result was that the majority of people within the work activities that are carried out often tend to present affects in the body area in greater quantities. 63.33% report discomfort in their hands or wrists when carrying out work activities. In addition, they allowed us to determine that in fact the majority of nursing professionals suffer from some type of musculoskeletal disorder. In conclusion, it should be stated that the main ergonomic risk factors that affect musculoskeletal disorders by nursing staff are usually when adopting positions in which the most frequent postures are the use of wrists, shoulders, ankles or feet and at their instead of lifting heavy objects which cause pain at the lumbar level.